1984
DOI: 10.1007/bf00994229
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic potential of sorghum (Sorghum bicolor): Isolation of seed germination inhibitors

Abstract: In Figure 2, there was a labeling error on the original drawing. On the left side Fraction III should be Fraction II and on the right, Fraction II should be Fraction III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Besides crops, weeds are also vulnerable to its allelopathic influence [16,36]. Sorghum toxicity is mainly determined by both hydrophilic phenols in herbage, as well as hydrophobic sorgoleone and its analogs exuded by the root hairs [37,38]. Therefore, sorghum herbage reach can be successfully used against weeds as a foliar spray as it is discussed in detail in the previous chapter.…”
Section: Sorgoleonementioning
confidence: 99%
“…Besides crops, weeds are also vulnerable to its allelopathic influence [16,36]. Sorghum toxicity is mainly determined by both hydrophilic phenols in herbage, as well as hydrophobic sorgoleone and its analogs exuded by the root hairs [37,38]. Therefore, sorghum herbage reach can be successfully used against weeds as a foliar spray as it is discussed in detail in the previous chapter.…”
Section: Sorgoleonementioning
confidence: 99%
“…Indeed, sorghum has been known to cause 'soil sickness' and affect the growth of other crops in rotation systems (Breazeale, 1924;Einhellig and Rasmussen, 1989;Forney et al, 1985;Putnam et al, 1983). Early studies reported that several classes of water-soluble compounds, such as the phenolics, may be responsible for these allelopathic properties, but these compounds are ubiquitous in plants and are not likely to be involved in the unique activity observed in sorghum (Alsaadawi et al, 1986;Lehle and Putnam, 1983;Panasiuk et al, 1986). On the other hand, 1 is an uncommon lipid benzoquinone with herbicidal activity produced exclusively by sorghum species .…”
Section: Sorgoleone Discovery and Allelopathymentioning
confidence: 99%
“…Several workers have examined the chemical composition of root exudates of sorghum (Guenzi et al, 1967;Lehle and Putnam, 1983;Alsaadawi et al, 1986;Panasiuk et al 1986). Netzly and Butler (1986) isolated hydrophobic p-benzoquinones from grain sorghum roots exudates, which were ultimately identified and named sorgoleone (Netzly et al, 1988).…”
Section: Introductionmentioning
confidence: 99%